Elementi di interfaccia per l’analisi di strutture murarie - Elio Sacco; Jessica Toti (Fracture and Structural Integrity)
The present paper deals with the modelling of the mechanical behaviour of masonry elements regarded as heterogeneous systems, made of mortar, bricks and interfaces. Thus, the adopted computational strategy consists in modelling the brick units, the mortar joints and the interfaces responsible for the mortarbrick decohesion mechanisms; to this end, a special interface model combining damage and friction is proposed. A numerical procedure, based on the backward Euler time-integration scheme, is introduced; the time step is solved adopting a displacement driven predictor-corrector scheme. Some numerical applications are performed in order to assess the performances of the proposed model and algorithm in reproducing the nonlinear response of masonry material due to damage localization. Finally, a masonry arch model is studied, comparing the numerical results with experimental ones; it is show the ability of the proposed model to simulate the global behaviour of the arch structure in term of ultimate load and collapse mechanism.